2020
DOI: 10.1093/jtm/taz104
|View full text |Cite
|
Sign up to set email alerts
|

Does age have an impact on acute mountain sickness? A systematic review

Abstract: Acute mountain sickness (AMS) is the most common form of illness at high altitude; however, it is still unclear whether age is a protective factor or a risk factor for the development of AMS in travellers. In recent decades, the number of travellers aged 60 years or older is increasing. Thus, the care of older travellers is a long-standing issue in travel medicine. This study aims to systematically review the current state of knowledge related to the effect of old age on the risk of AMS. Preferred Reporting It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 55 publications
(131 reference statements)
0
8
0
Order By: Relevance
“…Previous literature showed conflicting and inconclusive associations between age and AMS (Wang et al, 2010 ; McDevitt et al, 2014 ; Tang et al, 2014 ; Chan et al, 2016 ; Gonggalanzi et al, 2016 ; Cheng et al, 2017 ; Wu et al, 2018 ). This is predominantly due to the heterogeneity in study location, design, population, AMS diagnostic tool, and, most importantly, the small number of older adults included in the studies (Wu et al, 2018 ; Gianfredi et al, 2020 ). Studies that concluded older age as a protective factor have included more participants who were representative of the age group >55 years (Tang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature showed conflicting and inconclusive associations between age and AMS (Wang et al, 2010 ; McDevitt et al, 2014 ; Tang et al, 2014 ; Chan et al, 2016 ; Gonggalanzi et al, 2016 ; Cheng et al, 2017 ; Wu et al, 2018 ). This is predominantly due to the heterogeneity in study location, design, population, AMS diagnostic tool, and, most importantly, the small number of older adults included in the studies (Wu et al, 2018 ; Gianfredi et al, 2020 ). Studies that concluded older age as a protective factor have included more participants who were representative of the age group >55 years (Tang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Any disagreements about the eligibility of particular studies were resolved through discussion with a senior reviewer (MN). In line with previous studies [ 17 , 18 ], a standardized form was used to extract data from the included studies for the assessment of research quality and evidence synthesis. As in previous reviews [ 19 , 20 ], the extraction form was pre-piloted on five randomly selected eligible studies.…”
Section: Methodsmentioning
confidence: 99%
“…Oxygen availability, being restored along descent, leads, indeed, to a rebound of parasympathetic tonus [254]. Vagotonusinversely relates to age [255,256] and tends to be augmented by melatonin [257][258][259]. Enhanced vagal activity can lead to accidents by provoking failures in consciousness.…”
Section: Death In the Mountainmentioning
confidence: 99%